Identifying the effects of the stability of farmland transfer management rights on the use of organic fertilizer with different farmland scales and crop types - Zhou, Laiyou; Lu, Hua; Wu, Boying (Frontiers in Environmental Science, 2022)
Encouraging farmers to protect the quality of arable land is a focus of the current Chinese government. Enhancing the stability of arable land property rights is considered by the academic community to be an effective way to do so. Based on the survey data of 723 households in the hilly area of Jiangxi Province and using the probit model and robustness test methods, this paper examines the effect of stable farmland transfer management rights on farmers’ use of organic fertilizer and the differences in this effect with different management scales and crop types. The results show that stable management farmland transfer rights significantly encourage farmers to use organic fertilizer. Specifically, signing a written formal contract, increasing the contract registration rate, and extending contracts’ duration can increase farmers’ probability of using organic fertilizer, but whether there is a dispute in a farmland transfer has no significant impact on farmers using organic fertilizer. This study also finds that the impacts of stable arable land transfer management rights vary based on different characteristics of farmers using organic fertilizer. Stable arable land transfer management rights can encourage large-scale farmers and farmers planting grain crops to use organic fertilizer. To increase the stability of these rights, the local government should encourage farmers to sign formal written contracts, standardize their registration, and extend their duration.